Physical Properties and Prebiotic Activities (Lactobacillus spp.) of Gelatine-Based Gels Formulated with Agave Fructans and Agave Syrups as Sucrose and Glucose Substitutes - Rogelio Rodríguez-Rodríguez; Paloma Barajas-Álvarez; Norma Morales-Hernández; Rosa María Camacho-Ruíz; Hugo Espinosa-Andrews (Molecules, 2022)
This research developed model foods of gelatine-based gels, where carbohydrates from Agave tequilana Weber var. Azul (agave syrups or/and agave fructans) were incorporated into gel formulations as healthy sucrose and glucose substitutes. The sugars (sucrose and glucose) were substituted by agave carbohydrates (agave syrups and agave fructans), obtaining the subsequent gel formulations: 100% agave syrup (F2 gel), 100% agave fructan (F3 gel), and 50% agave syrup–50% agave fructan (F4 gel). The unsubstituted gel formulation was used as a control (F1 gel). The prebiotic activities, physical properties, thermal stability (HP-TLC), and texture of gelatine-based gels were evaluated. The gel formulations showed translucent appearances with approximately 36 g/100 g of water and water activities values between 0.823 and 0.929. The HP-TLC analysis validated that agave fructans did not hydrolyse during the thermal process of gels production. Gels produced with agave syrup and agave fructan (F2-F4 gels) provided higher hardness, gumminess, and springiness values (p < 0.05) than those produced with glucose and sucrose (F1 gel). Gelatine-based gel formulations displayed prebiotic activities correlated to the ability of Lactobacillus plantarum, Lactobacillus paracasei, and Lactobacillus rhamnosus to use agave carbohydrates as carbon sources. Based on the prebiotic effect and physical and textural properties, the F2 and F4 gel formulations displayed the best techno-functional properties to produce gel soft candies.